(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
Nearly 500 million people are injured worldwide every year by road traffic accident, of which more than 12 million lose their lives. Road traffic accidents (RTAs) have emerged as a major global public health problem of this century. The two wheelers now-a-days have great pick-up & high speed. Driving a two-wheeler is definitely risky than a four-wheeler. The risk to driver or pillion rider increases by many folds during the ride. Driving under the influence of alcohol is one of the important causes of road traffic accidents. Alcohol was implicated in nearly 1.8 million deaths globally, accounting for 3.2 % of total deaths, 2.5% of total years of life lost, 6% of total years of life disabled and 4% of the total disease adjusted life years. An attempt is made to find out role of alcohol and other related factors responsible for heavy casualty in road accidents.